(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
The third sector consists of non-profit organizations, non-governmental, whose purpose is to generate public and social services. These organizations can be characterized as charities, religious or community organizations, unions, arts organizations, professional associations and non-profit organizations. The Centro Cultural Escrava Anastácia (CCEA) is an association which aims to maintain the well-being of its members through the formation of associations of recreations, sports and clubs. This study seeks to analyze the degree of compliance of the CCEA with the accounting standards applied to the third sector. In this research, which is characterized as archival, we used a checklist consisting of aspects that refer to items of compliance verification, adapted as an instrument to verify the proposed disclosure. The data used refer to the entity’s bylaws and its financial statements for the year 2014 and 2015, which were obtained directly from the CCEA. The results suggest a general level of compliance of the financial statements of approximately 79.45% for the year 2015, confirming the need to improve the accounting disclosure using the specific norms related to the associations.